Side‐chain interactions in the regulatory domain of human glutamate dehydrogenase determine basal activity and regulation. (26th January 2015) - Mastorodemos, Vasileios; Kanavouras, Konstantinos; Sundaram, Shobana; Providaki, Maria; Petraki, Zoe; Kokkinidis, Michael; Zaganas, Ioannis; Logothetis, Diomedes E.; Plaitakis, Andreas
Abstract Glutamate Dehydrogenase (GDH) is central to the metabolism of glutamate, a major excitatory transmitter in mammalian central nervous system (CNS). hGDH1 is activated by ADP and L‐leucine and powerfully inhibited by GTP. Besides this housekeeping hGDH1, duplication led to an hGDH2 isoform that is expressed in the human brain dissociating its function from GTP control. The novel enzyme has reduced basal activity (4–6% of capacity) while remaining remarkably responsive to ADP/L‐leucine activation. While the molecular basis of this evolutionary adaptation remains unclear, substitution of Ser for Arg443 in hGDH1 is shown to diminish basal activity (< 2% of capacity) and abrogate L‐leucine activation. To explore whether the Arg443Ser mutation disrupts hydrogen bonding between Arg443 and Ser409 of adjacent monomers in the regulatory domain ('antenna'), we replaced Ser409 by Arg or Asp in hGDH1. The Ser409Arg‐1 change essentially replicated the Arg443Ser‐1 mutation effects. Molecular dynamics simulation predicted that Ser409 and Arg443 of neighboring monomers come in close proximity in the open conformation and that introduction of Ser443‐1 or Arg409‐1 causes them to separate with the swap mutation (Arg409/Ser443) reinstating their proximity. A swapped Ser409Arg/Arg443Ser‐1 mutant protein, obtained in recombinant form, regained most of the wild‐type hGDH1 properties. Also, when Ser443 was replaced by Arg443 in hGDH2 (as occurs in hGDH1), the Ser443Arg‐2 mutant acquired most of the hGDH1 properties. Hence, side‐chain interactions between 409 and 443 positions in the 'antenna' region of hGDHs are crucial for basal catalytic activity, allosteric regulation, and relative resistance to thermal inactivation. <boxed-text content-type="graphic" id="jnc13019-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Glutamate dehydrogenase (GDH) is central to the metabolism of the excitatory transmitter glutamate, and links it with carbohydrate metabolism in energy homeostasis and cell signaling. The isoform hGDH2, in contrast to hGDH1, is dissociated from GTP (guanosine triphosphate) control, has a reduced basal activity, but remains highly responsive to ADP/L‐leucine activation. Substitution of Serine (Ser) for arginine (Arg443) in hGDH1 diminishes basal activity (< 2% of capacity) and abrogates L‐leucine activation. We provide evidence that side‐chain interactions between 409 and 443 positions in the regulatory domain of GDH are crucial for basal catalytic activity, allosteric regulation, and relative resistance to thermal inactivation.